EFFECTS OF FUEL SUBSIDY REMOVAL ON ALLOCATIVE EFFICIENCY OF STAPLE CROP PRODUCTION IN GOMBE STATE, NIGERIA - Umaru Biye, Salihu; U. Musa, Rilwanu; A. Turaki, Musa; Mohammed, U. (FUDMA Journal of Sciences, 2025)
This study was carried out after fuel subsidy was removed, the aim is to examine effects of fuel subsidy removal on allocative efficiency (AE) of Staple Crop Production in Gombe State, Nigeria. Multistage, purposive and simple random sampling techniques were used to select 360 respondents. The data were analyzed using both descriptive statistics and inferential statistics. Results revealed that majority of the respondents were male (66.94%), adults with a mean age of 60 years, married (81.67%), having (54.44%) household size of 10 persons with a good literacy level of (89.73%). Coefficients of transportation cost, seeds, family labour and agrochemicals were all highly significant at 1%. Fertilizers weas at 5% while hired labour at 10% accordingly. The mean AE was 51%, sigma squared was significant at 10%, Gamma (γ) was 0.88 and significant at 10%. Constraints include but not limited to; high cost of petrol leading to inflation, high cost of transportation, labour, fertilizer, quality seeds. It was recommended that government should refine crude oil locally, exempt tax on agricultural inputs, establish mega agricultural store for subsidized inputs sale in the 774 local governments, revive extension services and also encourage farmers to join cooperatives.
Keywords: Allocative Efficiency; Fuel Subsidy Removal; Staple Crop Production